Principles of refrigeration - Dossat, Roy J. (New York: John Wiley & Sons Inc., 1961)
In this publication, the first four chapters deal with the fundamental principles of physics and thermodynamics upon which the refrigeration cycle is based. Chapter 21 treats electric motors and control circuits as they apply to refrigeration and air conditioning systems. Throughout this book, emphasis is placed on the cyclic nature of the refrigeration system, and each part of the system is carefully examined in relation to the whole.
Includes index: p. 535-544.
ne 9/05/2018
Arch
Keywords: Refrigeration and refrigerating machinery; Refrigeration - principles